Academic Self‐Perceptions and Academic Achievement in Chinese Children: A Multiwave Longitudinal Study. Issue 5 (14th March 2020) - Fu, Rui; Lee, Jinsol; Chen, Xinyin; Wang, Li
Abstract : This study examined reciprocal contributions between academic self‐perceptions and academic achievement. Data were collected each year in four consecutive years from a sample of children in China (initial N = 1, 156; 581 boys; initial M age = 9.33 years). Analyses using random intercept cross‐lagged panel models revealed that the effects of academic achievement on self‐perceptions tended to be more evident in lower grades and the effects of academic self‐perceptions on achievement tended to be more evident in higher grades. Latent growth curve analyses showed that the initial level of academic self‐perceptions and achievement moderated the growth of each other. The results indicate the contributions between academic self‐perceptions and achievement that occur in a progressive cascading manner in Chinese children.